2008
DOI: 10.7824/rbh.v7i2.61
|View full text |Cite
|
Sign up to set email alerts
|

Baixas doses de glyphosate e seus efeitos no crescimento de

Abstract: Resumo -Com o objetivo de verificar o efeito de baixas doses, simulando a deriva do herbicida glyphosate no crescimento e desenvolvimento inicial da Commmelina benghalensis foi realizado um trabalho em condições de casa-de-vegetação. A trapoeraba foi semeada superficialmente (aproximadamente 2 cm) em tubetes preenchidos com substrato. Após a germinação, deixou-se apenas uma planta por tubete e realizou-se aplicação dos tratamentos. Os tratamentos foram constituídos por diferentes doses de glyphosate, 2, 4, 8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
1
6
0
4
Order By: Relevance
“…Leaves dry mass production of common bean Xodo genotype increased linearly with the rise of glyphosate reduced doses ( Figure 1A), reaching the maximum value around 34.14% of increase in leaves dry mass acumulation for the glyphosate subdose of 12.96 g ha -1 . Similar result was found by Mechede et al (2008) when authors observed growth stimulus in leaves of Commelina benghalensis, with greater length and leaf area for all reduced doses used.…”
Section: Resultssupporting
confidence: 87%
“…Leaves dry mass production of common bean Xodo genotype increased linearly with the rise of glyphosate reduced doses ( Figure 1A), reaching the maximum value around 34.14% of increase in leaves dry mass acumulation for the glyphosate subdose of 12.96 g ha -1 . Similar result was found by Mechede et al (2008) when authors observed growth stimulus in leaves of Commelina benghalensis, with greater length and leaf area for all reduced doses used.…”
Section: Resultssupporting
confidence: 87%
“…These stimulatory effects have been observed in several species, such as Stellaria media (common chickweed), Tripleurospermum inodorum (scentless mayweed), Commelina benghalensis (tropical spiderwort), Hordeum vulgare (barley), Zea mays (maize), Glycine max (soybean), Eucalyptus grandis (eucalyptus), Pinus caribea (pine), Saccharum spp. (sugarcane), Coffea arabica L. (coffee), and Lactuca sativa (lettuce) …”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados com a aplicação de subdoses de glifosato em espécies como milho, soja, eucalipto, aveia, e em diferentes condições, apontaram, respectivamente, diversas reações, como estímulo de crescimento (Meschede et al, 2008;Velini et al, 2008;Silva et al, 2009;Gitti et al, 2011;Silva et al, 2012), aumento na área foliar, na altura das plantas e na produção vegetal , incremento na massa seca de plantas, no teor de tirosina e caroteno, e aumento na absorção de fósforo (Godoy, 2007;Meschede et al, 2011).…”
unclassified